Optimizing an Archimedean Screw Turbine (AST) at low water flow velocity for clean energy generation - Abd Rahim, Nuranisa Suhada; Yang, Chuan Choong; Mamat, Nur Fathin Najwa (Springer, 2025)
Clean energy can be generated utilizing Archimedean Screw Turbine (AST) with the aid of flowing water. In this work, the effect of velocity of water and inclination angle were investigated to determine the torque’s output. First, a simulation of screw turbine was performed using SolidWorks Flow Simulation. It was found that the screw turbine’s optimum design was with 3 blades and an angle of inclination of 25° to produce the highest torque. From the simulated result, a 3D printing process was utilized to fabricate the model to investigate the performance of the model via experimental test. From the experimental results, it was observed that 38° angle produces the highest torque at value 0.046 Nm at flow velocity of 0.06 m/s. After completing the experimental work, it shows that there is a difference outcome of most optimum angle between the simulation and experimental results. Simulation results indicate 25° is the optimum inclination angle while experimental results show 38° is the optimum inclination angle. This is because of overfilling phenomena that occurs during experimental works at inclination of 25°. The findings in this work indicate that a small-scale AST can perform at low flow velocity below 1 m/s and to be operated at 38° of inclination angle for clean energy generation.